Latent TGF-β1 Protects Against Crescentic Glomerulonephritis - Huang, Xiao R. (American Society of Nephrology, 2008)
Despite the critical role that TGF-β plays in renal fibrosis, transgenic mice that overexpress human latent TGF-β1 in the skin exhibit normal renal histology and function even though circulating levels of latent TGF-β1 are an order of magnitude higher than wild-type animals. In fact, latent TGF-β1 seems to protect against renal inflammation in a model of ureteral obstruction. It is unknown, however, whether latent TGF-β1 also has this effect in immunologically mediated forms of renal disease such as anti-GBM crescentic glomerulonephritis. We induced anti-GBM disease in wild-type and transgenic mice overexpressing latent TGF-β1 in keratinocytes. After 14 days, wild-type mice developed progressive crescentic glomerulonephritis with severe renal inflammation and fibrosis. In transgenic mice, proteinuria was reduced by 50%, renal function was preserved, and the formation of glomerular crescents was suppressed by 70%. In addition, transgenic animals had reduced renal inflammation, evidenced by a 70% decrease in the accumulation of T cells and macrophages, and reduced expression of renal IL-1β, TNFα, and MCP-1 by 70 to 80%. Progressive renal fibrosis was also prevented in the transgenic mice, and these protective effects were associated with elevated levels of latent, but not active, TGF-β1 in plasma and renal tissue. Renal Smad7 was up-regulated and both NF-κB and TGF-β/Smad2/3 activation were suppressed. In conclusion, mice overexpressing latent TGF-β1 in the skin were protected against anti-GBM crescentic glomerulonephritis, possibly via Smad 7-mediated inhibition of NF-κB-dependent renal inflammation and TGF-β/Smad2/3-dependent fibrosis.